Pengaruh Promsi Online Dan Kualiatas Pelayanan Terhadap Keputusan Pembelian Mahasiswa Manajemen Universitas Muhammadiyah Kupang - Nining Ramadani; Hanifa Djakaria; Upik Djaniar (Program Studi Manajemen - Fakultas Ekonomi - Universitas Muhammadiyah Kupang, 2022)
The purpose of this study was to determine the variables that influence the purchasing decisions of Management Students, Faculty of Economics, Muhamadiyah University, Kupang at the market palce shopee. These variables include online promotion, and service quality. The results showed that partially the online promotion and service quality variables had an effect on purchasing decisions. Likewise, simultaneously online promotion and service quality affect purchasing decisions.